The Contrastive Analysis of Ookii and Besar Adjective in Japanese and Indonesian - Tasman, Annisa Qamara; Sutedi, Dedi; Rasiban, Linna Meilia (Vocational College of Diponegoro University, 2023)
This study discusses the contrastive analysis of the adjective ookii in Japanese and the adjective besar in Indonesian. Both adjectives are contrasted in order to minimize the error of learners in the use of ookii, as the word ookii often appears in Japanese texts learned by learners. This study aims to describe and analyze the similarities and differences between ookii adjective in Japanese and besar adjective in Indonesian in terms of the study of semantic (meaning). To see the similarities and differences between ookii and besar adjectives, the equivalent technique was used which refers to linguistic phenomena by Koyanagi. Data in this study uses jitsurei from asahi.com, yahoo.co.jp, detik.com and tribunnews.com. The results of this study found 9 similarities and 2 differences between ookii adjective and besar adjective. The similarity of meaning contains relatively larger size, loud voice, fat, wide, plentiful, growing into adults, important, great influence, and serious problems. Meanwhile, there are two different meanings, namely being arrogant or being great and feeling free or not bothering with small things. In addition, this study found linguistic phenomena is the icchi and shinki phenomena. In the future, it is recommended to carry out further study using more varied data sources such as novels, newspapers, and magazines in order to find broader similarities and differences in meaning. Apart from that, further study can also examine the construction of sentences containing the adjectives ookii and besar.